Mechanisms of chemical degradation of cement-based systems proceedings of the Material Research Society's Symposium on Mechanisms of Chemical Degradation of Cement-based Systems, Boston, USA, 27-30 November 1995 - Scrivener, K. L.; Young, J. Francis (E&F Spon, 1997)
Deterioration of cement-based materials is a continuing problem, as it results in the substantial shortening of the lives of conventional concrete structures. The main costs result from poor performance and the need for early repair. With more advanced applications, where very long service lives are essential, such as the storage of nuclear waste, an understanding of the degradation processes in order to predict long term performance is very important. this book forms the proceedings of the latest Symposia at the Materials Research Society Autumn meeting in Boston.